A new case of Blastomicoma Blastomicoide Sudamericano - Sotelo, M. (1960)
Since 1937, qe P. T. WEISS and Peruvian ZAVALETA published the first case of deep mycosis called South American Blastomycosis, this condition has been the subject of study with us having so far referred 20 cases and 10 published under study and reason Thesis (OR), all from our Amazon.